THE ART OF QUEUE: PEMBENTUKAN STRUKTUR DRAMATIK DALAM FILM DOKUMENTER MENGENAI ANTRI DI BEBERAPA WILAYAH - Sumpena, Della Dwinanti (Institut Seni Budaya Indonesia Bandung, 2018)
This film entitled The Art of Queue packs an attitude that is applied to community activities in the form of queuing, which is combined into a whole story in the form of a documentary.Queuing is a unique and interesting activity because there are various expressions from people at the time of the process. Queuing is also strongly influenced by the ever-evolving cultural traditions. And also can not be separated from the shadow of the rules that follow. Although very little sanction is given if it is violated there will be penalties in it, both punishments that arise from other people, and also punishments that arise from within themselves.Activities that are already common in the community environment in general are compiled based on montage, with compilation made randomly. Combining several footage elements with a blend of transitions in them, which makes visual appearance into a whole. There is a blend of graphics, sketches, videos and audio in this film which ultimately forms a dramatic structure.There is a background mind about understanding tolerance, and a system from a line. This queuing system influences the reality of people's lives in Indonesia, in this case Bandung, Jakarta and Yogyakarta are samples of queue activities that occur in their communities.